Financing eHealth: Tsuji – Akematsu model revisited - Sheikh Abu Taher; Md. Kamal Uddin; Masatsugu Tsuji (International Telecommunications Society (ITS), 2018)
Information and Communication Technology (ICT) plays an essential role in the provision of health care system, especially for the rapidly increasing ageing population all over the world. In line with this, eHealth helps a significant role in the overall management of this data in terms of potential gains in efficiency, financial savings, quality of care and patient safety. But implementation of eHealth requires huge amount of capital at the beginning and problematic to determine quantitative benefits. Determination of quantitative and non-quantitative benefits is essential to support financing eHealth for policy makers. Thus, the study aims to explore and develop an accurate financing model for eHealth using Tsuji – Akematsu Model so that both the economic and non-economic benefits can be identified. Initially eHealth implementation requires extensive amount of cost but long-term usage, increasing number of users can reduce costs and increase benefits. Although the benefit to cost ration (B/C ratio) was estimated 0.25 or negative NPV in the model but if the services is promoted nationwide and more user use this service a positive NPV can be attainable.
Keywords: 330; eHealth; finance; health expenditures; economic evaluation; Japan